Motives for corporate cash holdings: the CEO optimism effect - Huang-Meier, Winifred; Lambertides, Neophytos; Steeley, James M. (My University, 2016)
We examine the chief executive officer (CEO) optimism effect on managerial motives for cash holdings and find that optimistic and non-optimistic managers have significantly dissimilar purposes for holding more cash. This is consistent with both theory and evidence that optimistic managers are reluctant to use external funds. Optimistic managers hoard cash for growth opportunities, use relatively more cash for capital expenditure and acquisitions, and save more cash in adverse conditions. By contrast, they hold fewer inventories and receivables and their precautionary demand for cash holdings is less than that of non-optimistic managers. In addition, we consider debt conservatism in our model and find no evidence that optimistic managers’ cash hoarding is related to their preference to use debt conservatively. We also document that optimistic managers hold more cash in bad times than non-optimistic managers do. Our work highlights the crucial role that CEO characteristics play in shaping corporate cash holding policy.
Keywords: Cash holdings; Cash holdings motive; CEO optimism; Liquidity